IMPLEMENTASI ONLINE LEARNING PROGRAM (OLP) DENGAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA UNTUK MENINGKATKAN PEMAHAMAN MATAKULIAH BIOLOGI UMUM PADA MAHASISWA PROGRAM STUDI PENDIDIKAN MATEMATIKA STKIP BINA INSAN MANDIRI SURABAYA - Noviana Desiningrum (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2015)
The research was conductedon for the first semester students of mathematics education faculty at STKIP-BIM Surabaya. The purpose of this research included:1) Obtain data on Implementation of Online Learning Program (OLP) with Media Multimedia-Based Learning, 2) Obtaindataonstudentcomprehension, 3) Obtainthe datapassing gradestudents, 4) Obtain data on Student Response. The research method which is used in this research is byusing the Classroom Action Research (Classroom Action Research). The results from this study include: view sof students' understanding forthe learning ability of OLP in the first cycle of 60.2 %, where asin the second cycle of 97% resulting in an increase in the percentage of 36.8% and the learning is successful. View ed from masteryof learning out comes in the first cycle was 68.5% while the second cycle of 80.5%, an increase of 12%. The  students response for the Online Learning Program (OLP) model based multimedia which is including positive category. From this case, it can be said already managed to apply the learning for the student.